TESTING OF MO-CONTAINING CATALYSTS APPLIED TO AL-, AL/ZR-PILLARED CLAYS DURING THE OXIDATIVE DEHYDROGENATION OF ETHANE TO ETHYLENE - K.A. Shorayeva; B.K. Massalimova; Yu.N. Bespalko; V.A. Sadykov (Academic Scientific Journal of Chemistry, 2020)
The development of an alternative method for the oxidative dehydrogenation of ethane to ethylene is an important task in the presence of a suitable catalyst. Mo-containing catalyst systems applied to Al-, Al/Zr-columnar clays were prepared. The textural characteristics of the synthesized Al-, Al/Zr-columnar clays differ from the textural properties of natural clay with an increase in their specific surface from ~54 m2 /g to ~215 m2 /g. The LaNbMo and VMoTeNb catalyst systems applied to l-, Al/Zrcolumnar clays showed higher activity and selectivity for oxidative dehydrogenation of ethane (ODH). A detailed characterization was achieved using XRD, adsorption of N2, SEM, BET to study the texture properties of the synthesized catalysts. The highest activity and ethylene selectivity were shown by 10% VMoTeNb/PILCs and 20% VMoTeNb/PILCs catalysts. The lowest ethylene selectivity was exhibited by 10% LaNbMo/PILCs and 20% LaNbMo/PILCs catalysts. The results obtained indicate that the application of LaNbMo and VMoTeNb polyoxide active phases to Al-, Zr-columnar clays can improve the physical and mechanical properties of these types of catalysts due to changes in both the nature of the crystalline phase and the catalytic properties in oxidation reactions.